Short versus long trans-pulmonary needle pathway for CT-guided percutaneous core needle biopsy of small sub-pleural pulmonary nodules - Das, Sushant Kumar; Chaudhary, Saurav; Pathak, Manish Raj; Pokhrel, Abishek (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: Short lesion-pleural distance allows little space for manipulation of biopsy needle with high risk of needle dislodgement into pleural space causing air leak and subsequently pneumothorax. This study compared short trans-pulmonary biopsy approach with long trans-pulmonary approach for small sub-pleural pulmonary nodule to determine approach with lesser complication and better diagnostic yield.Methods: A total of 65 patients who were undergoing CT guided biopsy for small (≤20 mm) sub-pleural (≤10 mm) pulmonary nodules were divided into two groups depending upon biopsy approach, i.e., long trans-pulmonary biopsy approach (group A, n=34) and short trans-pulmonary biopsy approach (group B, n=31). Diagnostic accuracy and complication rate between the groups were compared.Results: No significant difference was found between two groups in case of diagnostic accuracy (Group A vs Group B: 91.2% vs 87.1%; p=0.59). Pneumothorax rate was higher in group B (29.0%) compared to group A (14.7%), however, difference was not statistically significant (p=0.16). Among risk factors for pneumothorax, smaller lesion size (5-10 mm), short lesion-pleural distance (≤ 5 mm) and number of pleural passes (>1) was associated with significantly higher pneumothorax rate in group B compared to group A (71.4 vs 40% p=0.02; 85.7% vs 16.6% p=0.01; 100% vs 57.1% p=0.01 respectively).  Conclusions: Smaller sub-pleural pulmonary nodules render high risk of pneumothorax with the use of short trans-pulmonary pathway. If the nodule is very close to pleura and relatively smaller where one could not ensure access with single puncture, long trans-pulmonary pathway serves as safer option to avoid pneumothorax.